Employment over the life course and post-retirement social networks: a gendered perspective - Cohn-Schwartz, Ella [Verfasser]; Naegele, Laura [Verfasser] (My University, 2023)
„The present study examines how different lifelong employment patterns are related to social relationships in old age, and whether there are gender differences in the impact of lifelong employment patterns. The study was based on data collected among European adults as part of the Health, Aging and Retirement Survey in Europe (SHARE) and focuses on retired adults. The study combines data on social relationships, collected in 2015, with retrospective data on employment history (number of jobs and years of employment) collected in 2017. The findings show that adults who worked in more jobs had overall better structural characteristics of their later life networks - they had larger social networks and were more likely to include children and friends within those networks but less likely to include their spouse. On the other hand, working in more jobs was related to less emotional closeness with the network. These results varied between men and women; women who were involved in the labor market over their life had larger social networks and tended to include friends as confidants. Among men, working for more years was related to higher emotional closeness with the social network. The study may indicate a gendered pattern of social advantages and disadvantages to involvement in the labor market over the work course. Practitioners should consider the lifelong employment of adults to identify those who might be at risk of social isolation.“ (excerpt; BIBB-Doku)
Keywords: P 1.8 Ältere; G 2.4.4 Biografiegestaltung; G 2.4 Sozialer Wandel; G 2.4.5 Gender Mainstreaming; 370; 300; Erwerbstätigkeit; Rentner; Ruhestand; Soziale Beziehungen; Einflussfaktor; Arbeitsplatzwechsel; Arbeitsbeziehungen; Geschlechtsspezifische Faktoren